Detection of cellular material within handprints. Issue 1 (December 2019) - Kanokwongnuwut, Piyamas; Kirkbride, K. Paul; Linacre, Adrian
Abstract: A novel technique for the visualisation of cellular material has been published harnessing an external binding nucleic acid fluorescence dye, Diamond™ dye (DD), in combination with a digital fluorescence microscope. This technique can effectively detect cellular material on an object transferred by touch allowing targeted collection of latent DNA. Previous studies on the visualisation of touch DNA have focussed on transfer from fingertips only. Here we report on the visualisation of cellular material transferred via twenty different positions over the entire handprint. Three volunteers (a heavy, an intermediate and a light shedder) were asked to press their hands onto a plastic surface with medium pressure for 15 s at undefined time points post-handwashing, creating a complete handprint. DD was applied to the entire area and the presence of cellular material was recorded based on cells within 5 separate frames at each of the 20 positions. All tests were performed in triplicate such that the final dataset contained 1, 800 observed frames. This extensive study allows accurate monitoring of cellular transfer deposited by different parts of the hand. Our study highlights which areas of an individual's hand shed the greatest, or least, amount of cellular material. This simple process can act as a guide for DNA collection from items held within the entire hand, rather than only touched by the fingertips only, such as weapons, knives and steering wheels.